Web technologies : an allied of mathematics - Vaz, Estelita (2008)
It is well known that web technologies have, nowadays, a great influence on society behaviour, in particular on youth and university students. Therefore, universities are progressively adapting their courses in order to take advantage of the new existing technologies. This can be particularly useful and helpful when teaching mathematics to engineering students. We should not be aware of the fact that these students can be particularly enthusiastic about technologies. The Department of Mathematics for the Science and Technology, at the University of Minho (Portugal) is using the Maple TA system for several mathematics courses taken by engineering students of the first year of college, for instance in Calculus and Linear Algebra. We have big groups of students attending classes. On the other hand, they are not obliged to be present. The big number of students we are dealing with, and the fact that a significant percentage of which do not attend the classes regularly, for different reasons, creates conditions for implementing distance learning methods. Additionally, the Bologna education reform decreases the number of contact hours of the courses. To overcome this situation, we are creating new learning facilities that contribute to help the students on their individual work. The authors believe that it is quite challenging to redesign courses using web technologies (here Maple TA) under the environment described above. When using Maple TA to create learning objects one can have different goals: introduce a new topic, create tools for continuous practicing, edit complete question banks for a topic, assess the students or even obtain information about difficulties of the students on previous topics. Here we present our experience on constructing learning objects for courses on Calculus and on Linear Algebra. We wish to illustrate different perspectives used to create questions adapted to distinct pre-established goals. In particular, we explore randomization of variables, allowed by MapleTA, when creating questions which, under the traditional system (i.e., pen and paper) are equivalent to groups of questions.